Human immunodeficiency virus type 1 infection alters enzymatic and ultrastructural features of peripheral blood monocytes - Ali M Gabali (Thieme Medical and Scientific Publishers Pvt. Ltd., 2013)
Introduction: Human immunodeficiency virus-1 (HIV-1) infected monocytes are now believed to serve as a reservoir for HIV-1 infection, and to play a role in viral rebound phenomena in certain groups of patients who failed or stopped highly active antiretroviral therapy (HAART).Data characterizing the morphological changes of peripheral blood monocytes in HIV-1-infected individuals are limited. Materials and Methods: In this study, we collected monocytes from 21 asymptomatic HIV-1-infected individuals with CD4 count more than 500 cells/mm 3 and healthy individuals. The monocytes ultrastructural morphologic changes and α-naphthyl butyrate esterase (ANBE) activity were compared between the two groups. Results: In monocytes from patients infected with HIV-1, activity of α?naphthyl butyrate esterase?(ANBE) was markedly increased compared with normal monocytes. In both light microscopic and ultrastructural studies, the cytoplasm of monocytes from HIV?1?infected patients contained a haphazard appearing network of thin fibrils. Cell surface expression of the activation marker HLA?DR molecule was upregulated. There were no discernible differences between the cell surface expression of CD4, CD14, and CD16 molecules comparing normal monocytes to those from HIV?1?infected patients. -naphthyl butyrate esterase (ANBE) was markedly increased compared with normal monocytes. In both light microscopic and ultrastructural studies, the cytoplasm of monocytes from HIV-1-infected patients contained a haphazard appearing network of thin fibrils. Cell surface expression of the activation marker HLA-DR molecule was upregulated. There were no discernible differences between the cell surface expression of CD4, CD14, and CD16 molecules comparing normal monocytes to those from HIV-1-infected patients. Conclusions: Possibly, changes in the activity of ANBE along with a disrupted appearing cytoplasmic fibril network contribute to monocyte dysfunction in HIV-1-infected patients.